Best emollients for eczema (BEE) – comparing four types of emollients in children with eczema: protocol for randomised trial and nested qualitative study. Issue 11 (6th November 2019) - Ridd, Matthew J; Wells, Sian; Edwards, Louisa; Santer, Miriam; MacNeill, Stephanie; Sanderson, Emily; Sutton, Eileen; Shaw, Alison R G; Banks, Jonathan; Garfield, Kirsty; Roberts, Amanda; Barrett, Tiffany J; et al.
Abstract : Introduction: Atopic dermatitis/eczema affects around 20% of children and is characterised by inflamed, dry, itchy skin. Guidelines recommend 'leave-on' emollients that are applied directly to the skin to add or trap moisture and used regularly, they can soothe, enhance the skin barrier and may prevent disease 'flares'. However, the suitability of the many different emollients varies between people and there is little evidence to help prescribers and parents and carers decide which type to try first. Methods and analysis: Design: pragmatic, multicentre, individually randomised, parallel group superiority trial of four types of emollient (lotions, creams, gel or ointments). Setting: general practitioner surgeries in England. Participants: children aged over 6 months and less than 12 years with mild-to-severe eczema and no known sensitivity to study emollients. Interventions: study-approved lotion, cream, gel or ointment as the only leave-on emollient for 16 weeks, with directions to apply twice daily and as required. Other treatments, such as topical corticosteroids, used as standard care. Follow-up: 52 weeks. Primary outcome: validated patient-orientated eczema measure measured weekly for 16 weeks. Secondary outcomes: eczema signs (Eczema Area Severity Index) by masked researcher, treatment use, parent satisfaction, adverse events, child and family quality of life (Atopic Dermatitis Quality of Life, Child Health Utility 9D and Dermatitis Family Impact). Sample size: 520 participants (130 per group). Analysis: intention-to-treat using linear mixed models for repeated measures. Nested qualitative study: audio-recording of sample of baseline appointments and up to 60 interviews with participants at 4 and 16 weeks, interviews to be transcribed and analysed thematically. Ethics and dissemination: Ethics approval granted by the NHS REC (South West - Central Bristol Research Ethics Committee 17/SW/0089). Findings will be presented at conferences, published in open-access peer-reviewed journals and the study website; and summaries shared with key stakeholders. Trial registration number: ISRCTN84540529